The correlation of neutrophil-to-lymphocyte ratio with the presence and short-time curative effect of myasthenia gravis in children: a retrospectively study. (2nd September 2021) - Jiang, Zhi; Ning, Zeshu; Yang, Liming; Chen, Bo; Tang, Jingwen; Zhang, Jie; Fang, Hongjun; Xu, Rong; Guo, Feng; Chen, Mei; Sun, Kaisheng
Abstract: Objectives: This study aimed to investigate the influence of neutrophil-to-lymphocyte ratio (NLR) on the severity and short-time curative effect of myasthenia gravis (MG) in children. Methods: Data of 132 MG children were retrospectively analyzed, and data of 140 healthy controls (HC group) in the same period were collected. The data of both groups were compared and analyzed. Results: NLR of MG group was significantly higher than that of HC group ( Z = 2.644, p = 0.008). According to NLR level, patients were divided into 3 groups: N1 (NLR < 1.03), N2 (NLR 1.03-2.17), and N3 (NLR > 2.17). Significant differences in white blood cell counts, course of disease, uric acid, albumin and the time of hospital stay among the 3 groups were observed ( p < 0.05, 0.01). The results of logistic regression revealed that NLR (adjusted OR = 3.874, 95% CI 1.359-11.045, p = 0.011) was the risk factor of MG, and it was risk factor of higher QMG during admission (adjusted OR = 2.989, 95% CI 1.247-7.160, p = 0.014) as well. Using the NLR level for the MG diagnostic test, the area under the receiver operating characteristic (ROC) curve was 0.765 [95%CI (0.710-0.820), p = 0.000], with a cut-off value of 1.39, sensitivity of 0.833, and specificity of 0.479. Cox regression analysis suggested that NLR (N1: Wald = 9.262, p = 0.010, N2: HR = 12.267, 95%CI 2.432-61.863, p = 0.000, and N3: HR = 8.142, 95%CI 1.209-77.754, p = 0.032) was associated with poor efficacy at discharge. Elevated NLR was considered as an independent risk factor of poor outcomes during discharge. Conclusion: NLR could reflect disease severity and short time curative effect in children with MG to some extent. It may also be a potential marker in indicating diagnosis and severity of MG in children.